Assessing the Hepatotoxic Effects of Anti-Tuberculosis Treatment in Multi-Drug-Resistant Patients: Evidence from Fatimah Jinnah Hospital, Quetta - Muhammad, Essa; Andam, Gull; Haq, Noman; Saleem, Muhammad; Kaleem Ullah; Babar, Dawood Ahmed; Afzal, Muhammad; Jafar, Sara (Indus Journal of Bioscience Research, 2025)
Background: Hepatotoxicity continues to be a significant side effect of second-line anti-tuberculosis therapy, especially in patients with multidrug-resistant tuberculosis. Resource-constrained environments encounter increased difficulties owing to restricted monitoring and management capabilities. Methods: A retrospective cohort study was performed at Fatimah Jinnah Chest Hospital, encompassing 200 MDR-TB patients. Hepatotoxicity was characterised by alanine/aspartate transaminase values above three times the upper limit of normal. Statistical analyses encompassed t-tests, chi-square tests, and multivariable logistic regression to ascertain risk factors. Results: The incidence of hepatotoxicity was 12%. Patients with hepatotoxicity were older (mean age 45.5 vs. 37.8 years, p=0.041) and demonstrated significantly increased INR (1.50±0.30 vs. 0.76±0.25, p<0.001). Resistance patterns affected risk, with non-MDR strains (poly/XDR/Xpert-resistant) linked to increased risks (OR=5.61, 95% CI:0.40–77.98; p=0.014). Multivariable analysis identified INR as the most significant predictor (adjusted OR=395.7 per 1-unit rise; 95% CI:46.5–3366.8; p<0.001). Treatment outcomes were positive (82.5% cured), while adverse medication reactions were common, including gastritis (9.0%) and arthralgia (6.0%). Conclusion: Hepatotoxicity is common among MDR-TB patients undergoing second-line treatments, with increased INR and certain resistance types identified as significant risk factors. These findings highlight the imperative for stringent liver function surveillance and customised therapeutic approaches in high-burden environments to reduce hepatotoxic hazards and enhance treatment compliance. Improved pharmacovigilance and prompt intervention methods are essential for optimising MDR-TB management in resource-limited settings.